Treatment of fracture of mandibular condyle: A retrospective analysis of 45 cases - HU Yong; ZHU Jiadong; ZHAO Dayong (Kouqiang hemian waike zazhi)
[Objective:] To evaluate the treatment outcomes of mandibular condyle fractures managed by surgical and conservative procedures based on new classification. [Methods:] A total of 45 patients with 57 condyle fractures who were referred to Department of Stomatology in Suzhou Hospital, Affiliated Hospital of Medical School Nanjing University and Suzhou Kowloon Hospital from January 2012 to December 2021 were retrospected. The data were related to causes of injury, fracture classification, treatment methods, complications, and follow-up results. These data were then analyzed. [Results:] There were 11 females and 34 males, with an average age of 34.67 years (16-76 years). Traffic accidents were the main cause of injury (56%). There were 26 cases (35 sides) of intracapsular condyle head fractures. Among them, there were 13 cases (13 sides) of type A, 7 cases (11 sides) of type B, 1 case (1 side) of type C, 3 cases (6 sides) of type M and 2 cases (4 sides) of no displacement. There were also 12 cases (13 sides) of condylar neck fractures, and 7 cases (9 sides) of condyle base fractures. Ten cases of condylar head fractures including 4 cases of type B, 1 case of type C, 3 cases of type M and 2 cases of no displacement, and 3 cases of condylar neck fractures. Thirteen cases were treated conservatively. Sixteen cases of condylar head fractures including 13 cases of type A and 3 cases of type B, 9 cases of condylar neck fractures and 7 cases of condyle base fractures (a total of 32 cases) were treated surgically. Five patients were lost to follow-up, forty patients had follow-ups over 6 months. There were 3 cases of pain, 1 case of TMJ clicking, and 1 case of limited mouth opening in conservative treatments group. Postoperative complications showed 1 case of condyle resorption and 2 cases of facial nerve injury. [Conclusion:] Mandibular condyle fractuers should be considered in combinantion with new fracture classification and patient's general condition, and a reasonable individualized treatment plan should be selected.